2009
DOI: 10.1021/jf901826a
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Immunoaffinity Column for Aflatoxin Analysis Using an Organic Solvent-Tolerant Monoclonal Antibody

Abstract: An organic solvent-tolerant monoclonal antibody specific to aflatoxins B(1), B(2), G(1), G(2), and M(1) (AFB(1), AFB(2), AFG(1), AFG(2), and AFM(1)) was prepared. In an indirect competitive enzyme-linked immunosorbent assay, the half maximal inhibitory concentration (IC(50)) values were 1.9, 2.1, 2.1, 2.4, and 2.8 ng/mL for AFB(1), AFB(2), AFG(1), AFG(2), and AFM(1), respectively. Antibody reactivity was retained at 40% methanol concentration or at acetonitrile concentrations up to 40%. An immunoaffinity colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 21 publications
(32 reference statements)
0
23
0
Order By: Relevance
“…According to Uchigashima et al (2009), the binding capacity of the IAC was at least 400 ng (0.2 mL gel/column) for total aflatoxins (AFB 1 , AFB 2 , AFG 1 , and AFG 2 : 100 ng each). Recently, Sasaki et al (2014) reported the use of an IAC for STC cleanup because it shows cross-reactivity with aflatoxins and reported that the binding capacity of the IAC for STC was at least 200 ng/column and recovery exceeded 95 %.…”
Section: Methods Performancementioning
confidence: 99%
“…According to Uchigashima et al (2009), the binding capacity of the IAC was at least 400 ng (0.2 mL gel/column) for total aflatoxins (AFB 1 , AFB 2 , AFG 1 , and AFG 2 : 100 ng each). Recently, Sasaki et al (2014) reported the use of an IAC for STC cleanup because it shows cross-reactivity with aflatoxins and reported that the binding capacity of the IAC for STC was at least 200 ng/column and recovery exceeded 95 %.…”
Section: Methods Performancementioning
confidence: 99%
“…For instance, in developing IAC for zearalenone and ochratoxin clean-up, some research found that 1 mg antibody coupled with 1 mL of CNBr-activated sepharose 4B, as supporting material, provide 40 -50% stability toward high concentration of acetonitrile and methanol (Uchigashima et al 2009;Uchigashima et al 2012). The ratio used was obviously lower than the recommended ratio, but still the recovery percentage were satisfactorily ranging from 80 to 100%.…”
Section: Optimization Of Materials Using Iac Productionmentioning
confidence: 99%
“…68,69 A further improvement of the IAC technique was recently proposed by using organic solvent-tolerant monoclonal antibody for the production of IAC columns which have been applied to check for contamination of different spices: in particular, tolerance and good cleanup ability in the presence of acetonitrile and up to 60% methanol were observed. 70 Also, multifunctional column cleanup was applied to the detection of aflatoxins and ochratoxin in spices: for aflatoxins after extraction with acetonitrile:water (9:1), cleanup was performed using MultiSep 228 column for LC-FLD analysis, obtaining good recovery values (80-85%); for ochratoxin A, Mycosep 229 was used. 71 A simplified method was recently proposed for simultaneous determination of aflatoxins, dyes, and pesticides in spices, using acetonitrile for extraction via ultrasonic bath and, after dilution of the extract with pure water, direct injection in the LC-MS/MS system.…”
Section: Botanicals Spices and Herbsmentioning
confidence: 99%